Life history and host range of Sauris nr. purpurotincta, an unsuitable biological control agent for Chinese tallowtree. Issue 1 (2nd January 2017) - Fung, J.; Dyer, K.; Wheeler, G. S.
ABSTRACT: Foreign surveys in China discovered a defoliating insect species feeding on the leaves of Chinese tallowtree ( Triadica sebifera ), an invasive weed of the southeastern U.S.A. The life history of this species, Sauris nr. purpurotincta (Lepidoptera: Geometridae), was examined and larval no-choice and adult multiple-choice host range tests were conducted in quarantine to evaluate their suitability for biological control of Chinese tallowtree. The results indicated that the larvae have five instars and require approximately 22 days to complete development to the adult stage. Host range tests indicated that the larvae could not feed and complete development on most species tested. However, 40% of the larvae survived when fed leaves of Hippomane mancinella, a state-listed endangered species in Florida, and all larvae survived when fed Morella cerifera, a common native species of the southeastern U.S.A. Multiple-choice oviposition tests indicated eggs were laid on leaves of both a south Florida native plant Gymnanthes lucida and Chinese tallowtree. Considering this broad host range, this species will not be considered further for biological control of Chinese tallowtree in the U.S.A.